2019
DOI: 10.26464/epp2019037
|View full text |Cite
|
Sign up to set email alerts
|

Ring current proton scattering by low-frequency magnetosonic waves

Abstract: Magnetosonic (MS) waves are believed to have the ability to affect the dynamics of ring current protons both inside and outside the plasmasphere. However, previous studies have focused primarily on the effect of high‐frequency MS waves (f > 20 Hz) on ring current protons. In this study, we investigate interactions between ring current protons and low‐frequency MS waves (< 20 Hz) inside the plasmasphere. We find that low‐frequency MS waves can effectively accelerate < 20 keV ring current protons on time scales … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Until 15:31 UT, the MS wave, which is used to calculate the bounce‐averaged diffusion coefficients in Figures 4b and 4c, became so weak, leading to small calculated diffusion coefficients. Since the bounce‐averaged pitch angle diffusion coefficients are proportional to the wave spectral density (J. Yu et al, 2019), the observed strong MS waves before 15:20 UT are expected to effectively scatter energetic protons at the edge of the loss cones.…”
Section: Discussion and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until 15:31 UT, the MS wave, which is used to calculate the bounce‐averaged diffusion coefficients in Figures 4b and 4c, became so weak, leading to small calculated diffusion coefficients. Since the bounce‐averaged pitch angle diffusion coefficients are proportional to the wave spectral density (J. Yu et al, 2019), the observed strong MS waves before 15:20 UT are expected to effectively scatter energetic protons at the edge of the loss cones.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Recently, some attentions have been paid to the interactions between MS waves and ring current protons. The theoretical calculation of the diffusion coefficients has shown that MS waves can produce strong proton angle diffusion for ring current ions just on the edge of the equatorial loss cone (Fu et al, 2016; J. Yu et al, 2019). However, direct observational evidence of pitch angle scattering for ring current ions near the equatorial loss cone by MS waves has so far remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the scattering rates, the temporal evolution of electron pitch angle distributions can be obtained through performing the 2‐D Fokker‐Planck diffusion simulations (Yu, Li, et al, ). Following previous studies (e.g., He et al, ; Li et al, ; Shprits et al, ; Yu, Wang et al, ), the initial distributions of electrons are assumed to be F = e −( E − 0.02)/0.1 (sin α eq − sin α LC )/( pc ) 2 ( E is the electron energy in MeV, α LC is the loss cone), and the boundary conditions are taken as follows: F = 0 at α eq = α LC , ∂F / ∂α eq = 0 at α eq = 90°, F = constant at E = 10 keV and F = 0 at E = 10 MeV. Figure shows the electron temporal evolution diffused by chorus waves only (a–d), Z‐mode waves only (e–h), and combined diffusion (i–l) at the indicated times at L = 6 at Saturn.…”
Section: Electron Distribution Evolutionmentioning
confidence: 99%
“…The discrete and continuous nature of MS waves has been well‐explained by Chen LJ et al (2016) and SUN JC et al (2016a, b). Satellite observations indicate that MS waves are confined within a few degrees of the magnetic equator and located at 2 ≤ L ‐shell ≤ 8 (Perraut et al, 1982; Laakso et al, 1990; Ma QL et al, 2013), which are commonly believed to be excited by the ring distribution of ring‐current protons (Boardsen et al, 1992; Meredith et al, 2008; Chen LJ et al, 2010; Ma QL et al, 2014; Yu J et al, 2019b). MS waves typically have a very large wave normal angle (WNA) that is close to 90° and are nearly linear polarized (Kasahara et al, 1994; Chen LJ and Thorne, 2012; Min K et al, 2019).…”
Section: Introductionmentioning
confidence: 99%